Strategi Pembentukan Soft Skill pada Teaching Factory di SMK Warga Surakarta - Bima Prayoga Adiyatama; Valiant Lukad Perdana Sutrisno; Yuyun Estriyanto (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2026)
The large number of vocational high school graduates who cannot adapt to their jobs causes the Open Unemployment Rate (TPT) of vocational high school graduates to be the highest compared to other graduates. Various efforts have been made by the government to overcome this problem, one of which is by implementing TEFA. This study aims to (1) obtain an overview of the activities of forming and soft skills in TEFA SMK Warga Surakarta; (2) To find out what factors influence the success of forming and soft skills through TEFA at SMK Warga Surakarta. This study uses a qualitative descriptive approach with a case study method. The sampling techniques are purposive sampling and snowball sampling. Data collection techniques use interviews, observations, and documentation. The results of this study indicate that the formation of soft skills in TEFA SMK Warga Surakarta includes effective communication, public speaking, leadership, teamwork, management, work ethics, and adaptation. Factors that influence the formation of hard skills and soft skills at TEFA SMK Warga Surakarta include industry involvement, work culture, the role of teachers and their challenges, and strategies for overcoming obstacles.